Effect of Delay Order on Estimation Quality—Experimental Evidence on the Tendency to Consider Continuous Delays as Discrete Delays. (29th February 2016) - Größler, Andreas; Bleijenbergh, Inge; Vennix, Jac; McCardle‐Keurentjes, Marleen
Abstract : The purpose of the study is to test whether people make different estimations regarding the consequences of their decisions when a dynamic task is formulated as either a discrete delay or a continuous delay. We test the assumption that people have a tendency to treat continuous delays in real life situations as discrete delays. We created a dynamic task with two different conditions: hiring when personnel stay in an organisation for exactly 10 years (discrete delay condition) or when personnel stay on average for 10 years (continuous delay condition). The task was performed by 79 participants in an experiment. Findings show no differences regarding decisions being made, indicating that participants treat both discrete and continuous delays similarly. Because participants' estimations are substantially closer to the (simulated) system response when a discrete delay is involved, we assume that people have the tendency to treat all types of lags as discrete delays. The results were replicated with two additional experimental tasks that were (i) similar except with respect to task context and (ii) testing the understanding of the two delay types by additional control questions. Research implications are that perception of delay order and understanding consequences of different delay orders play a substantial role for controlling dynamic systems. Practical implications regard making delay order a salient characteristic in decision‐making tasks within organisations, for instance, in human resource management, and the training of managers to understand behavior of dynamic systems based on delay order in that system. Copyright © 2016 John Wiley & Sons, Ltd.